The Distributional Effects of Carbon Pricing in Türkiye - Zeynep Gizem Can; Cathal O'Donoghue; Denisa Maria Sologon (Institute of Labor Economics (IZA), 2025)
As middle income countries grow they see an increase in demand for energy. To avoid extreme climate change as these countries develop, there will be a need to decarbonise the increased energy consumption as they grow. We use the PRICES microsimulation model to examine the impact of carbon pricing across the income distribution in Türkiye. In particular we assess the joint distributional impact of combining both carbon taxation with revenue recycling. We evaluate both the relative performance of existing excise duties and additional carbon taxation. Despite the relative large change in the tax rate, replacing excise duties with carbon related excise duties has a relatively small distributional impact, with carbon taxes slightly less regressive than excised duties. Additional carbon taxes equivalent to exteuro30 per tCO2 are regressive, increasing inequality. However we find that revenue recycling has a greater impact on inequality than the tax itself, with targeted instruments reducing inequality, while flatter instruments when combing with the carbon tax do not fully compensate for the increased inequality from the carbon tax. Although the carbon tax reduced emissions, revenue recycling mitigated this impact with a trade off between redistribution and emissions reduction.
Keywords: Q58; C15; 330; carbon pricing; middle income countries; revenue recycling; microsimulation